Novel Observations of Peroxiredoxin-2 Profile and Protein Oxidation in Skeletal Muscle From Pigs of Differing Residual Feed Intake and Health Status - Amanda C Outhouse; Brian M Patterson; Edward M;. Steadham; Elisabeth J. Huff-Lonergan; Emma T Helm; Jack C. M. Dekkers; Kent Schwartz; Logan G Johnson; Nicholas K. Gabler; Steven M. Lonergan (Meat and Muscle Biology, 2021)
This study’s objective was to determine the impact of a dual respiratory and enteric bacterial health challenge on the antioxidant protein peroxiredoxin-2 (Prdx-2) profile and protein oxidation in the skeletal muscle of pigs from 2 lines that were divergently selected for residual feed intake (RFI). The hypotheses were that (1) differences exist in the Prdx-2 profile between 2 RFI lines and infection status and (2) muscle from less efficient high-RFI and health-challenged pigs have greater cellular protein oxidation. Barrows (50 ± 7 kg, N = 24) from the 11th generation of the high-RFI (n = 12) and low-RFI (n = 12) Iowa State University lines were used. Pigs (n = 6 per line) were inoculated with Mycoplasma hyopneumoniae and Lawsonia intracellularis (MhLI) on day 0 post infection to induce a respiratory and enteric health challenge. Uninoculated pigs served as controls (n = 6 per line). Necropsy was at 21 d post infection. Sarcoplasmic protein oxidation, various forms of Prdx-2, and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) content were determined. Neither RFI line nor infection status significantly affected protein carbonylation. Under nonreducing conditions, MhLI pigs had a greater amount of a slower-migrating GAPDH band (P = 0.017), indicating oxidative modification. Regardless of health status, the low-RFI pigs had less total Prdx-2 (P = 0.035), Prdx-2 decamer (P = 0.0007), and a higher ratio of hyperoxidized peroxiredoxin relative to Prdx-2 (P = 0.028) than the high-RFI pigs. The increased pool of active Prdx-2 in high-RFI pigs suggests greater oxidative stress in muscle in high- versus low-RFI pigs. The increase in oxidized GAPDH seen in muscle from MhLI pigs—particularly the high-RFI MhLI pigs—may be a response to the greater oxidative stress in the high-RFI MhLI. This work suggests that antioxidant proteins are important in growth and health-challenge situations.